2011
DOI: 10.1111/j.1439-0396.2011.01131.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition, in vitro digestibility and gas production of straws from different varieties and accessions of chickpea

Abstract: Chemical composition, in vitro digestibility and gas production of straw from four different varieties of Kabuli chickpea (Cicer arietinum) were studied. Kinetics of fermentation of straws from 19 different accessions of chickpea was also evaluated using gas production technique. Significant difference (p < 0.05) was observed in the yield of straw [from 1041 to 1174 kg dry matter (DM)/ha] from different varieties. The proportion of seed/straw from different varieties varied from 0.61 to 0.93. Crude protein, ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
14
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 18 publications
9
14
2
Order By: Relevance
“…Chickpea straw generally contains more protein, greater energy and lower cell wall contents than that of cereal straws (Aghajanzadeh et al, 2012;Kafilzadeh, 2012). Cell-wall of straw becomes mostly carbohydrates which is the most important fragment of by-products.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chickpea straw generally contains more protein, greater energy and lower cell wall contents than that of cereal straws (Aghajanzadeh et al, 2012;Kafilzadeh, 2012). Cell-wall of straw becomes mostly carbohydrates which is the most important fragment of by-products.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers (Ribeiro et al, 1990;Fekadu et al, 2010;Aghajanzadeh et al, 2012 andKafilzadeh, 2012) have reported in-vivo and in vitro Organic matter and CP digestibility of chickpea straw were found between 47.1-62% and 40-64% respectively. However there is little information about in situ rumen degradability of chickpea straw (Ørskov et al, 1992;Bruno-Soares, 2000;Aghajanzadeh et al, 2012 andKafilzadeh, 2012).The objective of this investigation was to identify chemical composition and degradation characteristics and ME of different chickpea lines and check cultivar straw. Agriculture -Food Science and Technology, 5(5): 459-463, 2017 460 (Anonymous, 2010).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Varieties 7 and 8 had the highest yield of DOM (2.9 ton/ha) while V12 produced the lowest DOM yield (1.9 ton/ha). Other factors known to affect the composition and digestibility of straw are variety and cultivar (Mould et al, 2001;Kafilzadeh & Maleki, 2011), environmental and seasonal effects (Mathison et al, 1999) and proportion of morphological fractions of the straw (Agbagla et al, 2001). The ME (MJ/kg DM) levels of straw from different varieties were calculated from the amount of gas produced at 24 h incubation with the supplementary analysis of CP.…”
Section: Resultsmentioning
confidence: 99%